Study of the contributions of non-specific and specific interactions during fluoxetine adsorption onto activated carbons - Valente Nabais, Joao (2012)
The adsorption of fluoxetine onto activated carbons (ACs) prepared from almond tree pruning by steam and CO2 activation under different temperature conditions (650– 9508C), was studied. In both series increasing the temperature caused an increase in the BET apparent surface area, yielding ACs with SBET up to 870 and 710m2 g 1 after steam and CO2 activation, respectively. Also, a slight widening of the porosity was found in both cases. In order to modify the functionality of the ACs, two of them were impregnated with triethylenediamine (TEDA) prior to the adsorption process, which caused a decrease in the AC apparent surface mainly due to micropore blockage. The fluoxetine adsorption isotherms at 258C showed maximum adsorption capacities between 110 and 224mgg 1. The adsorption isotherms were analyzed using Langmuir and Freundlich models. Although the impregnation reduced the pore volume, it did not cause a decrease in the fluoxetine maximum adsorption capacity, but a modification in the adsorption mechanism was observed.